The Red Petticoat Brigade: Mine Mill Women's Auxiliaries and the Threat from Within, 1940s-70s - Steedman, Mercedes (Whose National Security? Canadian State Surveillance and the Creation of Enemies, 2000)
Documents the RCMP's monitoring of the women's auxiliaries of the International Union of Mine, Mill and Smelter Workers in northeastern Ontario in the Cold War era.
Keywords: Intelligence service; Internal security; National security; Royal Canadian Mounted Police (RCMP); Subversive activities